Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia (University of Maribor Press, 2025)
This monograph covers an extensive array of topics related to special needs, talent, and giftedness in the Slovenian educational system. It consists of twelve insightful chapters written by twenty-three authors, mostly from the University of Maribor’s Faculty of Education. Addressing a wide range of professionals, the book examines innovative research and strategies to enhance the support and education of these special populations. The topics covered include speech and language therapy, reading adaptations and adjustments to music lessons for autistic students, the inclusion of children with special needs in folklore, and the identification and support of twice-exceptional students. It also discusses student involvement in school-home cooperation, early identification of mathematically gifted children, musical talent development, dance creativity in kindergarten, multilingual reading to expand vocabulary, and classroom design to encourage artistic expression. Overall, the monograph promotes a better understanding of these populations’ specific needs and encourages discussion about creating inclusive, supportive, and effective educational environments.